2011
DOI: 10.1111/j.1365-2362.2011.02522.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin receptor blockers are associated with a lower remodelling score of stenotic aortic valves

Abstract: ARBs were associated with lower aortic valve weight and less pronounced tissue remodelling. Further studies are needed to determine if ARBs could be used as a therapeutic avenue in AS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(20 citation statements)
references
References 38 publications
2
17
0
1
Order By: Relevance
“…Furthermore, AVC was assessed visually in the study of Roberts et al versus by a quantitative MDCT in the present study. On the other hand, a study showed in surgically explanted stenotic aortic valves that the fibrocalcific remodelling score was independently determined by the sex (male) and BAV 30. In the present study, we found that despite having higher MG, BAV patients had lower AVCd (p=0.01).…”
Section: Discussionsupporting
confidence: 44%
See 1 more Smart Citation
“…Furthermore, AVC was assessed visually in the study of Roberts et al versus by a quantitative MDCT in the present study. On the other hand, a study showed in surgically explanted stenotic aortic valves that the fibrocalcific remodelling score was independently determined by the sex (male) and BAV 30. In the present study, we found that despite having higher MG, BAV patients had lower AVCd (p=0.01).…”
Section: Discussionsupporting
confidence: 44%
“…Taken together, these data suggest that (i) AVCd is a good correlate of haemodynamic severity of AS in TAV and older BAV patients (≥51 years), (ii) BAV is independently related to AS severity despite lower AVCd level and (iii) fibrosis of aortic valve leaflets, which is not evaluated with MDCT, may play a significant role in determining AS severity particularly in younger BAV patients. This latter point is supported by the fact that despite having lower amount of calcium as evaluated by MDCT, BAVs have higher remodelling score 30. Hence, it is likely that compared with TAV, fibrosis is accentuated in BAV and alter valve haemodynamics significantly.…”
Section: Discussionmentioning
confidence: 94%
“…We previously reported that ARBs were associated with a lower remodeling of the aortic valve in 208 patients with CAVD [18]. In the present study we further refined our previous findings and found in 477 patients that ARBs were independently associated with a lower fibrosis score of the aortic valve, which is one component of the remodeling process along with mineralization.…”
Section: Discussionsupporting
confidence: 80%
“…The normal aortic valve is avascular and the formation of neovessels participates in the development of CAVD 14. To this end, stenotic BAVs demonstrate increased remodelling, neovascularisation and inflammatory infiltration compared to TAV, even when accounting for other risk factors for CAVD 33, 34. The expression of chondromodulin‐1 is markedly decreased in BAV compared to TAV 35.…”
Section: Pathobiologymentioning
confidence: 99%
“…Mineralised aortic valves are infiltrated by macrophages and T cells. In BAV, the density of inflammatory cells is higher when compared to TAV 33. Studies indicate that chronic inflammation of the aortic valve is one important process involved in the ectopic mineralisation of valvular tissue 40.…”
Section: Pathobiologymentioning
confidence: 99%